Analysis Design and Development of a Web-Based Human Resource Information System Using Agile Methodology at CV XYZ - Stefanie Quinevera; Desta Ovilini; Desiana Dian Malasari (SIMAK, 2026)
This study aims to analyze and design a web-based Human Resource Information System (HRIS) at CV XYZ, a company engaged in the distribution of fast moving consumer goods. The current human resource management process is still conducted manually, leading to inefficiencies, data inconsistencies, and delays in report generation. Data were collected through interviews, observation, documentation review, and literature study. The collected data were analyzed using a descriptive analysis approach to identify system requirements and existing problems. The system was developed using the Agile software development approach and modeled using Unified Modeling Language (UML). The results of this study produce an integrated HRIS that supports employee data management, attendance, payroll, leave, and shift scheduling within a single platform. The proposed system provides a structured solution for managing human resource data and demonstrates the potential to improve efficiency, accuracy, and accessibility of information. The system can also serve as a reference model for similar organizations facing comparable human resource management challenges.